Akses Sanitasi, Merokok dan Annual Parasite Incidence Malaria sebagai Prediktor Stunting Baduta di Indonesia - Zenderi Wardani; Dadang Sukandar; Yayuk Farida Baliwati; Hadi Riyadi (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The proportion of stunting above 20%, indicates that there are still public health problems in Indonesia. The impact of stunting not only affects stature with all the consequences of disruption of growth and development, but also affects the economic productivity of a country. The purpose of this study was to develop predictive models that are responsive stunting in children under-2 years in Indonesia. The development of the index model used mathematical formulations using the TPB/SDGs indicator and food environment indicators. Aggregate data from 16-time series were selected from 34 provinces in Indonesia in the span of 4 years (2015-2018). Furthermore, the model validation used the backward regression method with IBM SPSS Statistics version 22. The results showed that households have access to proper sanitation services (X9), smoking habits of the population aged ≥15 years (X14) and Annual Parasite Incidence (API) malaria per 1000 population (X12) was a responsive predictor of under-2 children stunting in Indonesia. The prediction model was expressed by the equation with an R2 value of 49.9% and Radj value of 44.9%. This study recommended fulfilling access to household sanitation facilities, especially in malaria endemic areas and households that have smoker family members.